Advances in cyber security : technology, operations, and experiences - Hsu, D. Frank (Derbiau Frank), 1948-; Marinucci, Dorothy (Fordham University Press, 2013)
The proliferation of social networking and advancement of information technology provide endless benefits in our living and working environments. However, these benefits also bring horrors in various forms of cyber threats and exploitations. This book collects the wisdom of cyber security professionals and practitioners from government, academia, and industry across national and international boundaries to provide ways and means to secure and sustain the cyberspace ecosystem. Readers are given a first-hand look at critical intelligence on cybercrime and security - including details of real-life operations. The useful knowledge and experience shared in this volume enables cyber citizens and cyber professionals alike to conceive novel ideas and construct feasible and practical solutions for defending against all kinds of adversaries and attacks. -- Publisher description.